APLIKASI PENANGGULANGAN PENYAKIT KANKER SERVIKS - Agus Ramdani Nugraha; Deni Ahmad Jakaria (LPPM STMIK DCI, 2015)
Developments in science and technology today have a wide impact on the level of human reliance on the information, tools and systems that can help facilitate human to solve problems in the work. This causes a human life can not be separated from the problems that are increasingly complex and require a higher knowledge to be able to handle it.Application design analasis cervical cancer is based on the analysis of the data of the results of the examination of the patient, the design of which will be made include: the design of disease data, causing the data design, the design of the data analysis results, design charts of the data analysis.With the application of this will make it easier to predict the performance of government estimates pendertia skyrocketing, so that the government can do a proper response and suppress the high number of patients in subsequent years.Keyword : Serviks, Application